The Influence of Marketing Strategy and Word of Mouth on Purchase Decisions at PT Inti Sanho Utama Teknologi, Medan - Wiselee, Ekin; Anggraini, Dewi; Adrian, Adrian; Ardiansyah, Ardiansyah (Cattleya Darmaya Fortuna, 2025)
Globalization and the development of information technology have changed the dynamics of marketing, requiring companies to continuously adapt and innovate. This study aims to analyze the influence of marketing strategy and word of mouth on purchase decisions at PT Inti Sanho Utama Teknologi, Medan. Using a quantitative approach, the study involved 34 respondents selected through purposive sampling, collecting primary data through an online questionnaire based on the Likert scale. Statistical analysis using multiple linear regression, normality, multicollinearity, and heteroscedasticity tests was performed with the help of SPSS software version 21.0. The results revealed that word of mouth had a significant influence on purchase decisions with a coefficient of 0.446 and a significance value of 0.028, while marketing strategy did not show a significant influence. The determination coefficient showed that marketing strategy and word of mouth were simultaneously able to explain 35% of the variation in purchasing decisions, with 65% influenced by factors outside the research model. These findings underscore the importance of personalized recommendations and consumer experiences in the context of technology distribution. The research contribution lies in the development of a more sophisticated conceptual framework for understanding the dynamics of purchasing decisions in the digital age, with practical implications for technology companies' marketing strategies. Research recommends focusing on building trust through word of mouth and authentic consumer experiences.